Turkestan Autonomous National Army - Gulomov Husanboy; Azamov Dilmurod (Periodica Journal, 2022)
This article discusses the Autonomy of Turkestan, the first national democratic state in our history, and its national army, who formed it and to what extent.
Keywords: Turkestan; Autonomy; Kokand; Ubaydulla